Educação ambiental em cursos de ciências contábeis da paraíba - Oliveira, Karla Eloisse Alencar de (2019)
In recent decades there has been a growing concern around the world on the environmental issue. Environmental Education has been pointed as an important tool that contributes to the participation of society in the preservation and conservation of the environment, thus promoting the diffusion of knowledge. Environmental Education is an interdisciplinary and transversal theme that should be adopted along with educational background. As stated in Law No. 9,795 / 99 (National Policy for Environmental Education), educational institutions must promote environmental education in an integrated manner with the educational programs they develop. At the same time the environmental dimension should also be included in teacher training curricula and in all subjects, in order to meet the objectives of the respective law. The present research aimed to analyze how the environmental theme has been worked in the presential courses of Accounting Sciences of the Public Universities of the State of Paraíba. This is a descriptive and qualitative research, as it described the characteristics of the subjects studied through the interpretation and relationship of the facts. Regarding the collection procedures, a field study was conducted with the Public Higher Education Institutions of the State of Paraíba, where the Coordinators and the Faculty of the Accounting Sciences course of the referred IES were interviewed. As data collection instruments, two interview scripts were used, one applied to the Coordinators and the other to the Faculty, composed by subjective questions. Also, a documental analysis was performed, which collected, through a checklist, information regarding the PPC's of the researched courses. The results obtained with the present study show that the challenges for an efficient insertion of the environmental theme in the curricula of Accounting Science courses in Paraíba are still great. The analysis carried out with the coordinators of the researched courses shows that the theme has been inserted in the courses. This insertion occurs through both the contents worked in the course subjects and through research carried out by the teachers of the HEI. The interviews with the teachers of the course indicate that they have no difficulty in inserting the theme in the subjects taught; They point out that they perform this insertion in an interdisciplinary and cross-sectional way and also ensure that students participate effectively and that they can apply the concepts discussed in class in practice. Through the analysis carried out with the PPCs of the researched courses, it was concluded that the coordinators' speeches differ in the sense that the coordinators point out that there are several teaching, research and extension activities, as well as specific events and actions related to the theme. , which cannot be observed in that document.